Optimalisasi Emis dalam Proses Data Base Pendidikan Diniyah dan Pondok Pesantren di Kementerin Agama Kabupaten Bangkalan - Savira Rahmania; Agus Ainul Yakin; Elvira Rohadatul Aisy (Program Studi Manajemen Pendidikan Islam, 2020)
Abstract: Education Management Information System (EMIS) is an education management information system to support planning and policy making in Islamic-based education programs. EMIS is a program that also provides real data to support policy makers. Technology and information as data collection bases have a very important role in supporting the achievement of educational goals. With the existence of EMIS, it is hoped that the incoming data can be more accurate and continuously updated so that it can be used as a basis for decision making. This study aims to determine the optimization of EMIS in the process of data base for diniyah education and Islamic boarding schools in the Ministry of Religion, Bangkalan Regency. As EMIS is an education database, it is hoped that the incoming data will be more accurate and updated to make it easier to find information. However, the Diniyah education and Islamic boarding schools in the Ministry of Religion, Bangkalan Emis Regency have not been able to be used optimally. One of these factors is that there are still many human resources who do not fully understand how to operate an EMIS, so that there are still many institutions that have not filled in the existing data on EMIS. The method used by the researcher is descriptive qualitative method, while the data collection technique uses interviews, observation and documentation. Keywords: EMIS, data dase, Islamic boarding school early education.